The impact of age on prostate cancer progression and quality of life in active surveillance patients. Issue 2 (29th November 2020) - Merrick, Gregory S.; Rohmann, Gabe; Galbreath, Robert; Scholl, Whitney; Fiano, Ryan; Bennett, Abbey; Butler, Wayne M.; Adamovich, Edward
Abstract: Objectives: To evaluate the impact of age on overall survival (OS), freedom from distant metastasis (FDM), rates of therapeutic intervention (TI), and quality of life (QOL) in active surveillance (AS) prostate cancer patients. Materials and methods: Three hundred and five consecutive, prospectively evaluated AS patients who underwent a staging transperineal template‐guided mapping biopsy (TTMB) prior to enrollment on AS were evaluated and stratified by age. Evaluated outcomes included OS, FDM, TI, and QOL to include urinary, bowel, sexual function, and depression. Post void residual (PVR) urine measurements were also followed. Repeat biopsy was based on PSA kinetics, abnormal digital rectal examination or patient preference. Results: Of the 305 patients, 290 (95.1%) were Gleason 3 + 3 and 15 patients (4.9%) were Gleason 3 + 4. The median follow‐up was 5.5 years (range 1‐14 years). At 10 years, TI was 0%, 1.0%, and 11.4% for patients ≤59, 60‐69, and ≥70 years of age ( P < .001). No patient has developed distant metastasis. The median time to TI was 4.71 years. No statistical differences in urinary function, bowel function, or depression were noted. Potency preservation was dependent on patient age. Conclusion: Within the confines of the follow‐up of our series, younger patients were less likely to proceed to therapeutic intervention. In addition, patient age did not adversely impact QOL outcomes.